Perempuan Perokok: Studi Pengguna Vape pada Dua Tempat Nongkrong di Kota Kendari - Faradila, Faradila; Hasniah, Hasniah (JURNAL KABANTI: Kerabat Antropologi, 2024)
This research aims to find out and describe the reasons why women use vape and the activities of women who use vape when hanging out at the Coffee Shop and Bat-Bat. The informants in this research were eight female vape users in two hangout places in Kendari City, namely the Coffee Shop and Bat-Bat. Data collection in this research was field research using observation and interview methods. The results of this research show that female vape users at the Coffee Shop and Bat-Bat hangout places use vape for various reasons, which can be influenced by two reasons, namely positive reasons and negative reasons. And what activities do female vape users do while hanging out at the Coffee Shop and Bat-Bat.